From Victory to Peace : Russian Diplomacy after Napoleon - Wirtschafter, Elise Kimerling (Book collections on Project MUSE., 2021)
"The book analyzes Emperor Alexander I's foreign policy in the years 1815-23, a critical period in the European restorations that followed the victory over Napoleon. It highlights Russia's integration into European society, understanding of European order, contribution to peacemaking, and perspective on what it meant to act in concert"--